215. Comparison of dose calculation using TG43 dose formalism and Collapsed-Cone Algorithm in vaginal and uterine brachytherapy. (December 2018) - Becci, D.; Bruno, A.; Leo, M.G.; Terlizzi, A.; De Zisa, G.; Mola, D.; Crastolla, A.; Marsella, A.R.; Silvano, G.
Abstract : Purpose: The aim of this study is to investigate differences in dose calculation resulting from the use of TG-43 formalism and Collapsed Cone Algorithm in vaginal and uterine brachytherapy (VUB). Methods: In this study we present an experimental evaluation of Oncentra Brachytherapy Advanced Collapsed-Cone Engine (ACE) using three different applicators: vaginal, Fletcher CT/MR with and without the interstitial applicator. We applied ACE algorithm first considering all of these structures composed of water (AW). Then we choose for them an uniform density value (UDV) and finally an HU-based density assignment (HUB). However, in HUB, a value of uniform density has been set for bladder, CTV and brachytherapy applicator. Evaluation has been performed in terms of D0.1 cc, D1cc and D2cc for rectum, sigmoid and bladder and in terms of the dose received from the entire volume (D100) for target volume (TV), in five patients undergoing intracavitary brachytherapy for cervical and uterine cancer over the course of 5 HDR fractions. Results: For all the three cases investigated, the main difference regard dose to D2cc of the rectum. In particular, we observed a percentage difference between −0.6% and 0.2% for AW case, between −4.2% and 0.9% for UDV case and between −4.6% and 0.6% for HUB case. The variation of D100 for TV is about between −0.2% and 0.3% in AW, between −1.8% and −0.3% in UDV and between −1.4% and −0.2% in HUB. Conclusions: From AW, UDV and HUB cases we note it seems to be not necessary to use ACE algorithms in VUB. Using them we can say it is crucial to select the predefined material closer to the electron density of each structure. Furthermore, it is necessary to establish when, for a given structure, it is preferable to use the HU or mass density assignment. For example, an incorrect selection of material could result to percentage differences up to −15% in D2cc of the rectum.